Assessing students’ errors in mathematical translation: From symbolic to verbal and graphic representations - Nurrahmawati Nurrahmawati; Cholis Sa'dijah; Sudirman Sudirman; Makbul Muksar (Institute of Advanced Engineering and Science, 2021)
Translation skills are very important possessed by students, but currently, there are still many students who have difficulty in translating between representations. The purpose of this study is to analyze students' errors in translating from symbolic representations to verbal and graphic representations. This research was descriptive study with qualitative approach. Tests are given to junior high school students. From the results of data analysis, it is obtained that in translating from symbolic to verbal forms (problems in daily life) that are following the given system of equations, students are still unable to make representations correctly. When students are asked to translate into graphical form, students are still unable to draw complete graphs and errors made by students are misinterpretation and implementation errors, so they cannot maintain the semantic congruence between source representation and target representation. Based on this, it is necessary to make a learning plan that can improve students’ ability to translate between representations.